Anti-Money Laundering and Combating the Financing of Terrorism : Review of the Quality and Consistency of Assessment Reports and the Effectiveness of Coordination. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This paper responds to a request from Executive Directors to review the quality and consistency of anti-money laundering and combating the financing of terrorism (AML/CFT) assessment reports prepared by the Financial Action Task Force on Money Laundering (FATF) and FATF style regional bodies (FSRBs), and the effectiveness of coordination with FATF/FSRBs. The review found a high degree of variability in the quality and consistency of reports prepared by the different assessor bodies as well as within the same assessor group. While a large majority of reports were of high- or medium quality with respect to key components of the assessments, the treatment of ratings gave rise to greater problems. A number of initiatives have been taken or are underway to improve the quality and consistency of assessments by all assessor bodies, including: the standardization of documentation, the strengthening of peer/internal reviews, and the intensification of assessor training.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: CFT Assessment; FATF Recommendation; FATF Style Regional Body; FSRB Practice; PP